Dog Owners' Perspectives on Canine Dental Health—A Questionnaire Study in Sweden - Enlund, Karolina Brunius; Brunius, Carl; Hanson, Jeanette; Hagman, Ragnvi; Höglund, Odd Viking; Gustås, Pia; Pettersson, Ann (Frontiers in Veterinary Science, 2020)
Periodontal disease is one of the most common diseases affecting dogs, with a reported prevalence of at least 80% in dogs over 3 years of age. However, there is a lack of studies regarding dog owners’ assessment of their dog’s dental health, and whether they perceive clinical signs often associated with periodontal disease, i.e. dental calculus, halitosis or mobile or lost teeth. A validated questionnaire survey was distributed to all Swedish dog owners with email addresses in the national registry (n=209,263). The response rate was 32%. The survey questions concerned opinions and practices regarding canine dental health, including assessment of dental health parameters and dog owners’ ability to examine their dog’s mouth. A construct (α =0.78) was used to investigate dog owners’ assessed symptoms of their dog’s dental health in relation to background factors. Half of the respondents rated their dog’s dental health as very good, however, one in four dog owners experienced difficulties when inspecting the dog’s teeth. The most common reason for this difficulty was stated to be an uncooperative dog. Almost half of the dog owners reported halitosis to some degree in their dog, and almost four in ten owners reported dental calculus. One in eight dogs had been previously anaesthetised for dental cleaning, and one in 12 dogs had experienced problems with gum disease, according to the owners. Owners’ assessment varied significantly with the dog’s age, weight, breed, breed group, sex, and concurrent disease. Owner-related factors that influenced the assessment of the dog’s dental health were age, gender, education, county (urban/rural), and whether they were breeders or not. Dog owners with smaller dogs, older dogs and certain breeds predisposed to periodontal disease assessed their dog’s dental health as worse than their counterparts, which is in agreement with previously reported higher prevalence of dental disease in these groups. This indicates that dog owners are able to perform relative assessment of their dog’s dental health status. Our results also highlight the need for routine professional assessment of periodontal health, as well as education of dog owners and training of dogs to accept dental care procedures.